Gender and residence differences in the association between social support and subjective well-being among Chinese oldest-old: A national longitudinal study. (January 2022) - Cheng, Gang; He, Simin; He, Qiong; Xie, Xiaowei; Tian, Gang; Jiang, Ni; Li, Chao; Min, Xianying; Li, Rui; Shi, Yan; Zhou, Tong; Yan, Yan
Highlights: Gender differences were found in the associations of living arrangements, contacts with others, children's frequent visits and telecommunications, community social services, caregiver when sick, and main medical expenses payer with subjective well-being. Residence differences were found in the associations of living arrangements, contacts with others, children's frequent visits and telecommunications, siblings' frequent visits, community social services, and main medical expenses payer with subjective well-being. Gender and residence-tailored interventions for social support are necessary to promote the well-being of the oldest old. Abstract: Objectives: This study aimed to explore the gender and residence (rural/urban) differences in the associations between the specific dimensions of social support and subjective well-being (SWB) among the Chinese oldest-old. Methods: This study included 12, 989 individuals aged ≥ 80 from 2011, 2014, and 2018 waves of the Chinese Longitudinal Healthy Longevity Survey. SWB was measured by ten items covering self-rated life satisfaction, positive emotions (optimism, happiness, personal control, and conscientiousness), and negative emotions (loneliness, anxiety, uselessness, depression, and boring feelings). Social support included the variables of marriage quality, living arrangements, contacts with others, children's and siblings' frequent visits and telecommunications, children and siblings living nearby, the main source of financial support, adequate financial support, social security and commercialized insurances, community social services, the caregiver when sick, and main medical expenses payer. Generalized estimating equation models were used to determine the effects of social support on the SWB. Results: Gender differences were found in the associations of living arrangements, contacts with others, children's frequent visits and telecommunications, community social services, caregiver when sick, and main medical expenses payer with SWB. Residence differences were found in the associations of living arrangements, contacts with others, children's frequent visits and telecommunications, siblings' frequent visits, community social services, and main medical expenses payer with SWB. Conclusions: There are gender and residence differences in the relationships between many dimensions of social support and SWB. Gender and residence-tailored interventions for social support are necessary to promote the well-being of the oldest old.